Factors associated with falls in elderly people with osteopenia or osteoporosis counter-referred from secondary care - Fernanda C. PINHEIRO; Edna A. REIS; Cristina M. RUAS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: Analyze the factors associated with the occurrence of falls in the elderly with low bone mineral density. Methods: Study performed between July 2014 and January 2016. Involved a cross sectional secondary data collection and telephone survey to counterreferred elderly patients from a secondary care service for primary care service in Belo Horizonte, Minas Gerais. Results: Were analyzed data from 2.020 patients and, among them, 1.120 were selected to participation in telephone survey phase. Respondents were predominantly female, aged 70-79 years, with normal or overweight body mass index, diagnosed with osteoporosis and family history of fractures. Regarding habits, the greater proportion did not practice physical activities, did not drink and smoke, did not sunbathe and had low intake of dark green vegetables. In addition, most of them had a fixed income, had been contacted by primary care after counterreferral and depended exclusively on the National Unified Health System. Higher proportion of falls was observed among women, in patients diagnosed with osteoporosis, with advanced age, who did not receive contact to return to the health center and in those with individual and family history of fractures. Statistical analysis demonstrate female gender, advanced age, individual or family history of fractures and low or no intake of dark green vegetables were factors that increased the risk of falls. Conclusion: Recommendations for improving health habits are simple actions and should be encouraged because they contribute to reducing the occurrence of falls and, consequently, it may lead to decrease morbidity and mortality of elderly patients.